The Effect of Profitability, Free Cash Flow, and Company Size on Debt Policy for Construction Companies - Devi Twi Jayanti; Khomsiyah Khomsiyah (Budapest International Research and Critics University, 2022)
The purpose of this study was to determine the effect of profitability, free cash flow, and company size on debt policy in building construction companies listed on the Indonesia Stock Exchange in 2017-2021. There are 55 data selected by the sample through purposive sampling method. The research method is using multiple regression analysis for hypothesis testing. The results partially show that profitability has a negative effect on debt policy, free cash flow has no effect on debt policy, while firm size has a positive effect on debt policy. Simultaneous research results where profitability, free cash flow, and firm size affect debt policy with a coefficient of determination of 0.560 which means that 56% of debt policy can be explained by independent variables (profitability, free cash flow, and firm size) while the remaining 44% is explained by another variable.